Increased risk of acute stress disorder and post-traumatic stress disorder in children and adolescents with autism spectrum disorder: a nation-wide cohort study in Taiwan - Li, Sung-Tao; Chien, Wu-Chien; Chung, Chi-Hsiang; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2024)
The children and adolescent with autism spectrum disorder (ASD) might be vulnerable when encountering traumatic events. The risk of acute stress disorder and post-traumatic stress disorder (PTSD) in the children and adolescents with ASD remains uncertain and is lacking large-scale evidence. Therefore, the present study aimed to investigate the association between ASD and the risk of developing PTSD and/or acute stress disorder. This was a retrospective and matched cohort study This is a provisional file, not the final typeset article with the data source from the National Health Insurance Research Database (NHIRD) in Taiwan, and was conducted from January 1, 2000, to December 31, 2015. Patients aged 18 years or under with a newly diagnosed of ASD were included, (n=15 200) and compared with the matched control group (n=45 600). The Cox proportional regression model was used so as to evaluate the risk of acute stress disorder and PTSD. A total of 132 participants developed either acute stress disorder or PTSD after a 15-year follow-up: 105 (0.691% or 64.90 per 100 000 person-years) in the ASD group and 27 (0.059% or 5.38 per 100 000 person-years) in the control group. Compared to the control group, the adjusted hazard ratio for the ASD group is significantly higher (25.661 with 95% CI =15.913-41.232; P < .001). This study suggested that patients with ASD are vulnerable to the development of acute stress disorder and PTSD. We therefore suggest that clinicians should pay more attention on the risk of PTSD/acute stress disorder in ASD individuals, with traumatic exposure.